Sistem Pemutusan Hubungan Kerja Pada Era Covid-19: (Tinjauan Perbandingan Hukum Ekonomi Syariah Dan Undang-Undang Ketenagakerjaan) - Mia Rosanita; Abdul Aziz; Fitri Adilla Zaqiyya (el hisbah: Journal of Islamic Economic Law, 2022)
In the midst of a pandemic due to Covid-19, many companies have laid off their employees. In fact, it is not certain that the related companies experience force majeure conditions. Layoffs are carried out on the basis of the company's anticipation to reduce the burden during the pandemic. This study will review the layoff system that occurred at P.T. Matahari Department Store Pekalongan in the Covid-19 era using a review of sharia economic law with the Labor Law Number 13 of 2003. The research method uses a type of field research with a qualitative research approach. From the process of data collection, analysis, and drawing conclusions, the results are obtained; 1) Based on a review of sharia economic law, the layoffs carried out by PT. Matahari Department Store Pekalongan during the pandemic era cannot be said by reason of force majeure that can cancel the contract agreement (ijarah). 2) In terms of the Manpower Law No. 13 of 2003, the company concerned has not experienced losses for two consecutive years due to the Covid-19 pandemic, only the company experienced a decrease in turnover during the pandemic. Thus, terminating employees by giving money in the amount of wages or compensation money is considered a middle way and the best solution between employers and workers, this refers to article 164 paragraphs 1 and 2 of the Labor Law. 3) PT. Matahari Department Store in terms of granting rights to laid-off employees has met the requirements. The company provides compensation in the form of money or in other forms as much as the company can afford. This has been mutually agreed upon as stated in the agreement and work contract signed by the two parties.